Identification of porcine circovirus type 2 by polymerase chain reaction and immunohistochemistry on archived porcine tissues since 1988 in Brazil Identificação do circovírus suíno tipo 2 por reação em cadeia da polimerase e por imunoistoquímica em tecidos suínos arquivados desde 1988 no Brasil - Ciacci-Zanella J.R. (2006)
Postweaning multisystemic wasting syndrome (PMWS) is of economical importance a disease caused by porcine circovirus type 2 (PCV2). A retrospective investigation was performed on paraffin-embedded organs samples from swine submitted to Embrapa Swine and Poultry Research Center between 1985 and 1998 for histopathologic diagnosis. A total of 25 cases were chosen from the archival collection of the Animal Health Laboratory at Embrapa Swine and Poultry based on characteristic pathological lesions of PMWS, such as lymphadenopathy, interstitial pneumonia, hepatitis and interstitial nephritis. The sections were investigated by nested-PCR (polymerase chain reaction) which used specific primers for the ORF2 sequence of the PCV2 and by immunohistochemistry using a monoclonal antibody specific for PCV2 capsid antigen. Virus specific DNA and antigen were detected in tissue samples of two out of 25 analyzed cases. The earliest positive sample originated from 1988. These results indicate that PCV2 is present in Brazil since 1988.